Impairment effects of creative ads on brand recall for other ads. (8th July 2019) - Jin, Hyun Seung; Kerr, Gayle; Suh, Jaebeom
Abstract : Purpose: The creativity-based facilitation effect, well documented by previous research, shows that creative advertisements (ads) are more memorable than regular (or less creative) ads, that is, creativity facilitates memory. This current research aims to extend our understanding by investigating the impact of creativity on regular ads and competitive advertising. It examines whether creative ads impair the memorability of regular ads to determine whether a "creativity-based impairment effect" exists. Design/methodology/approach: Three experiments were conducted. Experiment 1 tested creativity-based impairment effects in brand recall. Experiment 2 replicated and validated the impairment effect in recall, using a different presentation order of ads. In Experiment 3, effects of creative ads on competing vs non-competing brands were examined. Findings: Results found that creative ads impaired the brand recall of regular ads, creative ads impaired the recall of competing brands more than non-competing brands and creative ads were recalled earlier in top-of-mind recall positions. Research limitations/implications: Future research may look at whether different memory measures (e.g. recognition), different proportions of creative ads, and ads of familiar vs unfamiliar brands produce differential impairment effects. Practical implications: One suggestion from this research could be to not only copy-test your own brand's advertising, but also test the advertising of other brands so that the target ad's relative levels of creativity can be assessed before media buying. As a result of this testing, when the brand identifies any potential impairment effects, the identified creative ads could then be tracked in terms of media placement, providing a guide of where "not to schedule" advertising. Originality/value: This research makes an important theoretical contribution as the first to explore impairment effects in the context of creative advertising. In doing so, it offers important managerial insights for regular and competitive advertising.